(untitled) (Intent Research Scientific Journal, 2023)
In this article: New history of Uzbekistan, visual and applied arts, painting technology styles. Inspired by the artist’s art, a personal exhibition of painting and pottery samples, a composition of creative and thematic works, a presentation of a study guide, a scientific monograph, and a reflection on the value and importance of his works at the world level were discussed.